Structural basis of supercoiling-induced CRISPR–Cas9 off-target activity - Quentin M. Smith; Sylvia Whittle; Ricardo J. Aramayo; Daniel E. Rollins; Adam S. B. Jalal; Deborah I. Egharevba; Kyle L. Morris; Alice L. B. Pyne; David S. Rueda (Nature, 2026)
Abstract CRISPR–Cas9 is a powerful genome-editing tool 1 , but genome-wide off-target activity can hinder therapeutic applications. Negative supercoiling ((−)SC) has been implicated in off-target activity, but a molecular-level understanding is lacking. Here, using (−)SC DNA minicircles, we observe supercoiling-driven structural defects in the DNA that are resolved by Cas9 binding. Cryo-electron microscopy structures of Cas9 bound in both the on-target and off-target configurations highlight that the Cas9 HNH domain is poised in a more catalytically competent conformation. New DNA–RNA mismatch geometries are accommodated across the protospacer and structural plasticity in the protospacer adjacent motif distal region of the protospacer is topology dependent. Together, our study reveals the molecular basis for (−)SC-induced Cas9 targeting and provides a framework for the design of next-generation high-fidelity CRISPR effectors with topological context.